Penguatan Peran Negara dalam Implementasi Demokrasi Lokal di Indonesia - Author: Asrinaldi A. (Universitas Islam Indonesia, 2006)
This article aims to elaborate the role of state on implementing democracyat the local level. State, in which, often representing by government, facing dilema. In one hand, role of state is needed to keep democratization on the right track. It means that state must guarantee its citizen will not behave anarchism. Other hand, if state's role is too far, it can also threats its citizen's freedom. Therefore, this article want to show what aspect of political elite consderation in making strong state and have role in local autonomy as a part of local democracy in Indonesia through implementing Law No 32/2004.